Break point volume - Sweetenham, B. (1999)
From the author: `Break Point Volume` is a concept that I have used to describe and plan training programs that seek to maximise individual training response based upon annual training and competition demands of age-group swimmers. These demands progressively change during the process of maturation. It appears that long-term success as a mature senior swimmer is more likely if the developmental process follows an established course. A swimmer`s career might be characterised by three phases of training. `Break Point Volume`? It is optimum volume performed at optimum skill level achieved through participation in a maximum number of training sessions at controlled intensities. There are several important training relationships that count. The age of an athlete is perhaps the least considered factor in advancing athletes from one training squad to another. Whatever criteria is used it should be based upon both skill and commitment and on future achievement, not solely upon past achievement.